(untitled) (International Journal of Tissue Repair, 2025)
Background: Characterized by chronic duration and impaired healing, diabetic foot ulcers (DFUs) impose significant burdens in terms of morbidity, mortality, and economic cost. The limited effectiveness of current standard of care (SOC) approaches highlights the need for novel and cost-effective therapeutic strategies. Methods: An interim analysis of this multicenter, prospective, randomized controlled modified platform trial evaluated efficacy of multiple cellular, acellular, and matrix-like products (CAMPs) plus SOC versus SOC alone in achieving complete closure of hard-to-heal DFUs in 12-weeks. Results: Due to the early stage of this trial, percent area reduction at four weeks was used as a measure of success. For the dual layer matrix (Complete AA, Samaritan Biologics, LLC, Cordova, TN, USA) the PAR at 4 weeks was -15.3% compared to SOC at -11.1%. For the perforated tri-layer graft (MOST, Samaritan Biologics, LLC, Cordova, TN, USA) the PAR at 4 weeks was -32.5% compared to the -11.1% for SOC. Conclusion: This interim analysis demonstrates favorable treatment effect for CAMPs compared to SOC alone.